Artikel Keminatan siswa dalam mengikuti ektrakurikuler bola voli di Sekolah Dasar Negeri Roja 1: Keminatan siswa dalam mengikuti ektrakurikuler bola voli di Sekolah Dasar Negeri Roja 1 - jehartu, inovensius (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The purpose of this study was to determine how much factors influence students' interest in participating in extracurricular volleyball at SDN Roja 1, Rukun Lima Village, South Ende District, Ende Regency, East Nusa Tenggara Province. This study is a descriptive study using a survey method. The subjects of the study were students who participated in extracurricular volleyball at SDN Roja 1 as many as 39 children. The instrument used was a questionnaire, with a reliability coefficient of 0.953 and to analyze the data, quantitative descriptive statistics were used with percentages. The results of the study showed that students' interest in participating in volleyball extracurricular activities at SDN Roja 1, Rukun Lima Village, South Ende District, Ende Regency, East Nusa Tenggara Province. Most of them were in the low category of 56.40%, followed by the high category of 35.9%, then the very high category of 5.10%, and the very low category of 2.6%. So it can be concluded that students' interest in participating in volleyball extracurricular activities at SDN Roja 1 was mostly in the low category.